LIGHTLIKE HYPERSURFACES OF AN INDEFINITE (α, β)-TYPE ALMOST CONTACT METRIC STATISTICAL MANIFOLD WITH AN (l, m)-TYPE CONNECTION - Bhatti, Shagun; Kaur, Jasleen (IndoMS, 2024)
This paper aims to present the theory of hypersurfaces for a novel class of manifolds called an indefinite (α, β)-type almost contact metric statistical manifold or trans-Sasakian statistical manifold with an (l, m)-type connection. The study delves into the analysis of screen semi-invariant lightlike hypersurfaces within this framework. Specific conditions on the recurrent and Lie recurrent structure tensor field have been established. Additionally, illustrative examples are provided to enhance the comprehension of the introduced concept.